2016
DOI: 10.18697/ajfand.75.ilri01
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of aflatoxin consumption on animal health and productivity.

Abstract: Malnutrition is a major problem in East Africa and animal source foods could provide essential protein and micronutrients to help alleviate this. The livestock sector is rapidly growing and intensifying in response to increased consumer demand for animal source foods. However, the ability of the livestock sector to contribute to improving nutritional security is constrained by a number of factors, including contaminants in animal source foods and feeds. Globally, mycotoxins (especially aflatoxins) are the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Long-term exposure to aflatoxins is a major risk factor for liver cancer [ 18 ]. In animals, chronic exposure to aflatoxins is associated with weight loss and reproductive problems [ 19 – 21 ]. Particularly in pigs, the associated clinical signs are lethargy, hypothermia and icterus [ 22 – 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exposure to aflatoxins is a major risk factor for liver cancer [ 18 ]. In animals, chronic exposure to aflatoxins is associated with weight loss and reproductive problems [ 19 – 21 ]. Particularly in pigs, the associated clinical signs are lethargy, hypothermia and icterus [ 22 – 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…All animal species including the honeybees are susceptible to aflatoxicosis, but the outbreak occurs mostly in pigs, sheep, and cattle (Atherstone et al, 2016). Poultries are more sensitive to aflatoxin than mammals.…”
Section: Species Involvedmentioning
confidence: 99%
“…They are regularly implicated in toxic syndromes in animals and humans (Charoenpornsook and Kavisarasai, 2006;Stasiewicz et al, 2017). The word aflatoxin is the combination of 3 words "a" for Aspergillus genus, "fla" for the species flavus and toxin, meaning poison (Atherstone et al, 2016;Bakırdere et al, 2012). Although aflatoxins have been a problem throughout history until 1960, they have been recognized as significant contaminants within agriculture (Unnevehr and Grace, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, transfer into eggs could only be shown for the highest dose given the hens, and a transmission rate of 5000:1 has been estimated (Oliveira et al 2000). Fish species vary from highly susceptible to resistant, and honeybees are relatively resistant (Atherstone et al 2016).…”
Section: Impact On Livestock Productivitymentioning
confidence: 99%